2017
DOI: 10.1186/s41200-017-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

Range extension of the sesarmid crab Clistocoeloma villosum along the eastern Pacific coast of the Izu Peninsula, Japan

Abstract: Background: The Pacific coastline along the southern Izu Peninsula, Japan, is strongly influenced by warm tropical waters of the Kuroshio Current. A new easternmost record of the near-threatened sesarmid crab Clistocoeloma villosum is reported from the southern part of Izu Peninsula. Methods: The present study was conducted in August 2014 and February 2015, on tidal flats in the mouth of the Aono River, draining the southern part of Izu Peninsula. Crabs were collected by hand on the tidal flat substrate, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…The recorded population of C. villosum matches the descriptions of Yuhara et al [49] and Komai et al [50] and was found in two stony mangrove patches on the north eastern coast. This species has been previously recorded through a wide Indo-Pacific range [49]. A single female of N. pontianacense was found in the western coast mangroves, while large populations are found on artificial oyster reefs near the forest, suggesting that this small species is not a strict mangrove dweller.…”
Section: New Records For Hong Kong Mangrove Associated Faunasupporting
confidence: 89%
See 1 more Smart Citation
“…The recorded population of C. villosum matches the descriptions of Yuhara et al [49] and Komai et al [50] and was found in two stony mangrove patches on the north eastern coast. This species has been previously recorded through a wide Indo-Pacific range [49]. A single female of N. pontianacense was found in the western coast mangroves, while large populations are found on artificial oyster reefs near the forest, suggesting that this small species is not a strict mangrove dweller.…”
Section: New Records For Hong Kong Mangrove Associated Faunasupporting
confidence: 89%
“…H. sasekumari is one of the few pilumnids inhabiting mangroves and our record represents the new northernmost limit of its distribution [48]. The recorded population of C. villosum matches the descriptions of Yuhara et al [49] and Komai et al [50] and was found in two stony mangrove patches on the north eastern coast. This species has been previously recorded through a wide Indo-Pacific range [49].…”
Section: New Records For Hong Kong Mangrove Associated Faunasupporting
confidence: 83%
“…Clistocoeloma villosum is generally regarded as uncommon in Japan, except for the southern Ryukyu Islands where the species is treated as near-threatened (Japanese Association of Benthology 2012; Ministry of the Environment 2017). In 2014, it was recorded on the southern Izu Peninsula, an approxi-mately 350 km eastward extension of its previously-known distribution range of the tidal flat of Waka River Estuary in the Kii Peninsula (Karasawa et al 2006;Yuhara et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The sesarmid crab Clistocoeloma villosum (A. Milne-Edwards, 1869) is widely distributed in the Indo-Pacific oceans, including Madagascar, Sumatra, New Guinea, Australia, the Caroline and Samoan Islands, Japan, and Jeju Island in Korea (Tesch 1917;Crosnier 1965;Komai et al 2004;Lee et al 2010). In Japan, the crab has been recorded on the central and southern Ryukyu Islands, Kyushu, Shikoku, the Kii and Izu Peninsulas and Shimane Prefecture in Honshu mainland (Kishino et al 2001;Shokita et al 2002;Komai et al 2004;Kawakubo et al 2005;Ministry of the Environment 2005;Karasawa et al 2006;Miura & Jitsumasa 2010;Wada 2013;Maenosono & Saeki 2016;Osawa et al 2017;Yuhara et al 2017). Clistocoeloma villosum is generally regarded as uncommon in Japan, except for the southern Ryukyu Islands where the species is treated as near-threatened (Japanese Association of Benthology 2012; Ministry of the Environment 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation